Bankruptcy Codes and Innovation - Acharya, Viral V.; Subramanian, Krishnamurthy V. (Review of Financial Studies, 2009)
We argue that when bankruptcy code is creditor friendly, excessive liquidations cause levered firms to shun innovation, whereas by promoting continuation upon failure, a debtor-friendly code induces greater innovation. We provide empirical support for this claim by employing patents as a proxy for innovation. Using time-series changes within a country and cross-country variation in creditor rights, we confirm that a creditor-friendly code leads to a lower absolute level of innovation by firms, as well as relatively lower innovation by firms in technologically innovative industries. When creditor rights are stronger, technologically innovative industries employ relatively less leverage and grow disproportionately slower.